Controlling the southern root-knot nematode (Meloidogyne incognita Chitwood) with grafted and resistant pepper varieties - Mándoki, Z. (International Journal of Horticultural Science, 2010)
Newly bred resistant bell pepper varieties and those grafted onto resistant rootstock s were tested in soil severely infested with southern root-knot nematode [Meloidogy11e incognita (Kofoid and White) Chitwood] in unheated plastic house and compared to varieties on their own roots, in order to evaluate the efficiency of this environmentally friendly control method. 'Cinema F I ' carrying the N gene yielded significantly more than the two susceptible varieties. Varieties grafted onto resistant rootstocks outyielded those on their own roots although to different extent, which was not always significant. At the end of the vegetat ion period the roots of the rootstocks were undamaged and the roots of some resistant varieties were slightly infected. whereas the roots of susceptible varieties were severely damaged. According to our result  . both the use of resistant varieties and grafted plants offer an effective and environmentally safe way of controlling M. incognita.